Comparison of patterns of convergence among "emerging markets" of Central Europe, Eastern Europe and Central Asia - Joanna Poznańska; Kazimierz Z. Poznański (Comparative Economic Research. Central and Eastern Europe, 2015)
Based on analysis of economic growth indicators for 1989-2014, this article distinguishes the "emerging markets" of Central and Eastern Europe (with Russia included), from the other economies that fall in the broad 'emerging markets' category. Following the post-1989 reforms, the countries of the region share many of the same typical institutional features as other "emerging economies", but not necessarily the associated economic outcomes. What characterizes "emerging economies" is that they grow fast enough to systematically close the distance dividing them from the advanced economies, creating convergence. Departing from this pattern, Central and Eastern Europe (and Russia) have so far fallen short in terms of the growth rates, and the region as a whole has not made much progress in catching up. By more than doubling its national product Poland is the only notable exception in the region, although Slovenia may fit in the same category. At the other extreme, some of the economies actually lost two decades in terms of reducing the gaps, and some even fell further behind (e.g., Serbia, Ukraine). These findings have potentially serious implications for economic theory in general and for the presumption that globalization processes act as a unifying developmental force.
Keywords: 330; globalization; convergence; Central and Eastern Europe; "Emerging Markets"; "Income Distribution"; "Ownership Structure"